PARADIGMA KEILMUAN DAN FILSAFAT PENDIDIKAN DALAM PEMIKIRAN IBNU SINA - Nisa'atun Nafisah (PERADA, 2022)
The current crisis in the world of Islamic knowledge and education has resulted in the scientific tradition becoming static, so that Islamic education has not shown its full role in creating an advanced civilization. Islamic education as a goal, tool for change, and social transformation should be directed to accommodate local culture and be future-oriented, namely religious and modern. In Ibnu Sina's view, education should aim to explore and develop the potential of students. The concept of Ibn Sina's thought that education is carried out in stages and given according to their expertise and in accordance with the characteristics: potential, interests and talents of students. Some of Ibn Sina's thoughts on education can and have become material for consideration in the implementation of education in Indonesia because the concept of education conveyed by Ibn Sina is in line with the values of Islamic teachings which originate from the Qur'an and Sunnah. By relevating Ibn Sina's thoughts today, it is hoped that education in Indonesia will develop and be able to achieve the goals of national education contained in the Law on the National Education System.